PhET Simulation in Electrostatics Learning for Enhancing Higher-Order Thinking Skills: A Systematic Literature Review - Paramita Putri Apriyani; Ni Ketut Anggriani; Dewa Dwi Pranahita; Sintya Dewi Lestari (Indonesian Journal of Applied Science and Technology, 2026)
Modern physics education emphasizes the development of higher-order thinking skills, including critical thinking and problem-solving, alongside conceptual understanding. Static electricity, being an abstract topic, often presents difficulties and gives rise to student misconceptions. PhET Interactive Simulations serve as a digital learning medium that enables the interactive visualization of electrical phenomena, thereby allowing students to explore concepts and conduct virtual experiments. This study conducted a systematic literature review to examine the integration of PhET in static electricity instruction and its impact on developing students' critical thinking and problem-solving skills. A literature search was performed across Google Scholar, ERIC, and ScienceDirect for publications spanning 2015–2025, resulting in 21 selected articles for qualitative analysis. The findings indicate that the utilization of PhET enhances conceptual understanding of static electricity, critical thinking abilities, problem-solving skills, and student engagement in learning. The interactive visualizations within PhET correlate with improvements in the critical thinking dimensions of analysis, evaluation, and inference, as well as the problem-solving stages of understanding the problem, devising strategies, and evaluating solutions. These findings confirm that PhET Interactive Simulations can serve as an effective alternative learning medium to support the development of higher-order thinking skills in abstract physics topics.